2012
DOI: 10.1371/journal.pone.0049550
|View full text |Cite
|
Sign up to set email alerts
|

Silent Damage of Noise on Cochlear Afferent Innervation in Guinea Pigs and the Impact on Temporal Processing

Abstract: Noise-exposure at levels low enough to avoid a permanent threshold shift has been found to cause a massive, delayed degeneration of spiral ganglion neurons (SGNs) in mouse cochleae. Damage to the afferent innervation was initiated by a loss of synaptic ribbons, which is largely irreversible in mice. A similar delayed loss of SGNs has been found in guinea pig cochleae, but at a reduced level, suggesting a cross-species difference in SGN sensitivity to noise. Ribbon synapse damage occurs “silently” in that it do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
71
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 25 publications
16
71
0
Order By: Relevance
“…Thus, the present study examined the effects of noise-induced silent damage on ribbon synapses in neonatal mice during the early onset of hearing. The present results demonstrated that noise exposure shortly after birth resulted in similar but less marked damage to the ribbon synapses than has been observed in previous studies conducted in adult mice (Kujawa and Liberman, 2009;Lin et al, 2011;Liu et al, 2012;Shi et al, 2013). However, in contrast to adult animals, the loss of ribbon synapses progressed continuously in the young mice for more than 1 month following exposure to noise.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…Thus, the present study examined the effects of noise-induced silent damage on ribbon synapses in neonatal mice during the early onset of hearing. The present results demonstrated that noise exposure shortly after birth resulted in similar but less marked damage to the ribbon synapses than has been observed in previous studies conducted in adult mice (Kujawa and Liberman, 2009;Lin et al, 2011;Liu et al, 2012;Shi et al, 2013). However, in contrast to adult animals, the loss of ribbon synapses progressed continuously in the young mice for more than 1 month following exposure to noise.…”
Section: Introductionsupporting
confidence: 79%
“…The floor of the cage was 60 cm below the horns of one low-frequency woofer and one high-frequency tweeter, and electrical Gaussian noise was delivered through the two loudspeakers after power amplification. The acoustic spectrum of the sound was distributed mainly below 20 kHz, as described previously (Liu et al, 2012), and the frequency range for sound density 10 dB below the peak was between 3 and 14 kHz. The noise level was monitored using a 0.25-inch microphone linked to a sound level meter (microphone: 2520, sound level meter: 824, Larson Davis; Depew, NY, USA).…”
Section: Noise Exposurementioning
confidence: 87%
See 3 more Smart Citations